VALIDITY AND RELIABILITY OF THE INSTRUMENT ON THE IMPACT OF PARENTAL INVOLVEMENT ON MALAYSIAN PRIMARY PUPILS’ PERFORMANCE IN ENGLISH LANGUAGE (Practitioner Research, 2023)
The study aimed to assess the impact of parental involvement on Malaysian primary pupils’ performance in English language. A survey served as the research tool. The data collection for this study was conducted through a survey using a self-administered questionnaire. Google Forms online questionnaire was administered. SPSS software was used for analysis. Findings revealed that parental involvement have a significant and positive impact on the Malaysian Primary pupils’ performance in English language. The study recommended that schools should work to foster positive attitudes towards education by emphasizing the importance of education and celebrating academic achievements. Schools should consider individual pupils’ needs and provide tailored support to help them succeed. Schools and parents should work collaboratively to support pupils’ academic progress.